Perceptions of High School Students on AI Chatbots Use in English Learning: Benefits, Concerns, and Ethical Consideration - Ji Eun Lee; 맹은경 (Journal of Pan-Pacific Association of Applied Linguistics, 2023)
This study explored high school students’ perceptions of using AI chatbots in English learning. Specifically, it aimed to gauge the breadth of chatbot utilization and discern perceptions surrounding potential challenges linked to their use. Thirty students from a high school took part in the survey. Data analysis involved frequency, mean and an independent sample t-test. The findings are as follows. First, students recognized the importance and value of chatbots highly and perceived their usability positively. However, their previous experience with chatbots did not sway this perception. Second, students perceived using chatbots in English learning as very beneficial. Especially, those with chatbot usage experience have a more positive perception compared to those without experience. Third, students were relatively aware of potential ethical issues with using chatbots. They were particularly concerned about plagiarism and copyright issues and potential personal information breaches regardless of their experience with chatbots. They also perceived potential educational issues, fearing over-reliance on chatbots might hinder their exploratory learning or lead to copying assignments directly, missing out on learning opportunities. However, those without experience were more skeptical than those with experience. The implications and suggestions derived from these findings are also discussed.
Keywords: AI chatbots; perceptions; educational use; ethical issues